TOWARD THE CHARACTERIZATION OF THE EFFECTIVE STRUCTURAL FEATURES AND LANGUAGE FUNCTION OF ENGLISH USED BY THE BIOLOGY TEACHERS OF THE JUNIOR HIGH SCHOOLS TO CONDUCT VARIOUS INSTRUCTIONS - Herminingsih, Dwi Ima (Jurnal BONOROWO, 2014)
Using English as a medium of instruction provides linguistic benefits to the students. English which is used can elevate vocabulary, grammar and language functions of English. Besides, the students get  more chances to practice  writing, speaking, reading and listening during teaching and learning activities. Under this belief, the teachers are prescribed to be competent not only in content of subjects but also English. The teachers possession of  vocabulary, grammar, and language functions is a must.It is only with the clarity of English,  the teachers can help the students comprehend what the teachers feel think, instruct, command, describe, explain, clarify and so forth. This research project works with the identification of structural features and language function of English used by 3 selected Biology teachers of different Junior High Schools who are competent in English and the content of subject. This research is a qualitative design.Abstrak:Penggunaan Bahasa Inggris sebagai bahasa pengantar dalam proses kegiatan belajar mengajar dapat memberikan manfaat untuk meningkatkan kemampuan bahasa Inggris siswa. Siswa mendapatkan pengetahuan tambahan  tentang kosa kata  dan kaidah bahasa Inggris dari materi atau referensi yang sedang dipelajari, bahasa inggris yang dipergunakan guru dan teman. Selain dua  manfaat tersebut kemampuan siswa membaca, berbicara,  menulis serta mendengarkan akan dilatih ketika mereka harus mengerjakan tugas-tugas gurunya seperti membuat laporan praktikum, berdikusi, tanya jawab dan mempresentasikan hasil kerjanya. Dalam perspektif ini, guru harus memiliki kemampuan di bidang kosa kata, kaidah bahasa dan kemampuan menggunakan dua komponen bahasa sesuai dengan tujuan intruksionalnya seperti misalnya menjelaskan materi, bertanya, memberi tugas dan lain-lainnya sehingga tujuan belajar pembelajaran dapat dicapai. Penelitian ini mengidentifikas tipe komponen dan kaidah-kaidah bahasa Inggris yang bisa membantu siswa memahami apa yang disampaikan guru dalam kegiatan belajar mengajar yang dipergunakan guru Sekolah Menengah Pertama bidang biologi.  Tiga guru bidang biologi yang memiliki kompetensi bahasa inggris dan